Morphological changes in the vicinity of detached breakwater at Sungai Haji Dorani, Peninsular Malaysia - Hashim, Roslan; Kamali, Babak; Hashim, Ahmad Mustafa; Ismail, Zubaidah (2010)
Human activities in the coastal zones of Malaysia for the last fifty years had impacted its coastline. Serious efforts had been planned and implemented to improve or stabilize these affected areas. One of the relevant agencies, the Forestry Research Institute of Malaysia (FRIM), has carried out several coastal rehabilitation projects along the coast of Malaysia. In one of the projects, mangrove replanting was initiated to restore the depleting mangroves due to development projects and illegal harvesting activities. A detached breakwater was introduced to shelter a mangrove restoration area in Sungai Haji Dorani, on the west coast of Peninsular Malaysia. Construction of the breakwater on this muddy coast was successfully completed in July 2008. One of the main objectives of the breakwater was to facilitate sediment accretion behind the breakwater. The morphological changes in the vicinity of the breakwater have been monitored on a quarterly basis between July 2008 and December 2009. Numerical simulations with the 2DH model MIKE 21 have then been carried out. Field monitoring indicates that a significant volume of sediments was deposited in the lee of the breakwater, which is in good agreement with the results of the numerical simulations.